The concept of Europe as a cultural and religious identity - Shehu, Fatmir Mehdi (2018)
The long discussion on the making of Europe’s identity, from a political, economic, cultural or religious aspect, has paved the way for the unity of European nations as well as created many misconceptions in the mind-set of both the élite and the masses, the developed and undeveloped nations. The worry about the absorption of core principles of one’s culture within European community and the superiority of a high or an élite culture towards popular culture or low culture has created numerous obstacles for the construction of Europe’s cultural identity. The thrust of this paper is to study the concept of Europe as a cultural identity, which is very essential for the unity of Europeans, as well as for its motivation for its members to have a peaceful sense of self and co-existence. This contributes to their overall wellbeing and brings them closer together regardless of their differences. The formation of Europe’s cultural identity was examined by looking first at the development of major concepts, like “Europe,” “European culture,” “European language,” “cultural identity,” and second the essential elements of Hellenic, Roman, Christian, and scientific traditions. The descriptive and analytical methodologies have been employed in this paper. The findings have given insights to the reality of the unity of European nations under the banner of culture.